The role of curcumin in modulating nutritional status and susceptibility to Mycoplasma pneumoniae infection in children - Liu, Chun-Jing; Liu, Wei; Yang, Hong-Xiu; Li, Li-Hua (Frontiers in Pharmacology, 2025)
BackgroundMycoplasma pneumoniae remains a leading cause of pediatric respiratory infections, often resulting in prolonged symptoms, hospitalization, and systemic inflammation. Curcumin has been proposed as an adjunctive therapy due to its anti-inflammatory and immunomodulatory properties. This study retrospectively evaluated the association between adjunctive curcumin supplementation and clinical, immunological, and nutritional outcomes in children with confirmed M. pneumoniae infection.MethodsWe performed a retrospective observational study of children aged 1–12 years at Beijing Luhe Hospital (September 2023–May 2024). Based on charted treatment, 160 patients were categorized into a curcumin-supplemented group (n = 80; standardized 95% curcuminoids, 20 mg/kg/day, with antibiotics) or a control group (n = 80; antibiotics alone). Outcomes included duration of fever/cough, hospitalization, severe complications, inflammatory markers—C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α)—pathogen-specific antibodies, and nutritional indices (body mass index [BMI], hemoglobin, serum albumin). Adverse events (AEs) were summarized.ResultsBaseline characteristics were comparable between groups (all p > 0.05). The curcumin group had shorter fever (3.2 ± 1.1 vs. 4.5 ± 1.3 days, p = 0.01) and cough durations (5.4 ± 2.0 vs. 7.1 ± 2.5 days, p = 0.02), lower hospitalization rates (1.25% vs. 10.0%, p = 0.02), and fewer severe complications (2.5% vs. 12.5%, p = 0.03). Greater reductions were observed in CRP (−9.6 ± 5.1 vs. −1.8 ± 4.7 mg/L, p = 0.011), IL-6 (−15.1 ± 6.3 vs. −2.5 ± 5.8 pg/mL, p = 0.01), and TNF-α (−9.6 ± 5.4 vs. −1.7 ± 5.1 pg/mL, p = 0.03), with a larger increase in M. pneumoniae-specific antibodies (+30 ± 15 vs. +5 ± 12 AU/mL, p = 0.001). Antibiotic use (6.5 ± 1.8 vs. 7.8 ± 2.0 days, p = 0.014) and total recovery time (8.2 ± 2.1 vs. 10.5 ± 2.5 days, p = 0.001) were shorter in the curcumin group. Nutritional indices showed improvement in hemoglobin (p = 0.01) and serum albumin (p = 0.02), while BMI showed a non-significant increase (p = 0.368). AE incidence was low and similar (6.3% vs. 8.8%, p = 0.55). In multivariable regression, curcumin remained independently associated with shorter recovery (β = −1.2, p = 0.001).ConclusionCurcumin might be a safe and well-tolerated adjunct to standard antibiotic therapy in children with M. pneumoniae infections, potentially improving clinical outcomes, reducing inflammation, and supporting nutritional status.